ANALYSIS OF THE IMPACT OF TAX REFORM ON TAXPAYER PERCEPTION TAX ON SERVICES AT JEMBER PRATAMA TAX OFFICE - Fitriana, Aliyyah Desy; Gardina Aulin Nuha; Nina Martina (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the influence of tax reform on taxpayers' perception of the quality of services received. The tax reform implemented in Indonesia is expected to increase the efficiency and transparency of tax administration, which in turn affects taxpayers' perception of tax agencies. Method: Using a quantitative method through a survey of taxpayers at KPP Pratama Jember, this study identifies the service factors obtained by taxpayers, such as reliability, empathy, physical evidence of service, and guarantee of adequate administrative needs. Results: The results of the study show that tax reform followed by real changes in services, including increased transparency, speed, and quality of interaction between officers and taxpayers, has a significant positive influence on taxpayer perceptions. These findings also indicate that better services can improve taxpayer compliance levels and support the overall success of tax reform. Novelty: This study suggests that the government continues to develop a service system that is more responsive and in accordance with the needs of taxpayers to strengthen the impact of tax reform.